MANAGEMENT STRATEGY DESIGN WITH SWOT ANALYSIS TO ENHANCE THE COMPETITIVENESS OF ROBBY BARBERSHOP IN PEKANBARU CITY - Ramdani, Devinda; Suci, Rama Gita; Ameliya, Ameliya Gita; Murtaib, Agum Gita (Jurnal Manajemen, 2025)
This study aims to provide and improve the competitiveness of Robby Barbershop Pekanbaru, which has been established for seven years, again facing tight competition that continues to change. Using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), the research method used is descriptive with a qualitative approach. Data were collected through semi-structured interviews with the use of interview guidelines as the main tool for collecting information. The resulting strategies include four approaches (1) S-O Strategy (maximizing strengths to take advantage of opportunities), (2) W-O Strategy (improving weaknesses by using opportunities), (3) S-T Strategy (utilizing strengths to face threats) and (4) W-T Strategy (reducing weaknesses and avoiding threats). This study provides insight into the importance of adapting management strategies for MSMEs in facing the dynamics of business competition. In a situation in order to continue to advance and develop, they need an effective marketing strategy